The dynamics of fiscal policy in Algeria: Sustainability and structural change - Abderrahim Chibi; Sidi Mohammed Chekouri; Mohamed Benbouziane (Journal of Economic Structures, 2019)
This study focuses on the empirical tests for the sustainability and solvency of fiscal policies in Algeria using a nonlinear model approach, based on quarterly data from 1963Q1 to 2017Q1 on the Algerian budget balance-GDP. Empirical evidence indicates that the adjustment behavior of the budget balance has nonlinear characteristics in the form of a Logistic model depending on the oil price. On the other hand, unit-root tests (linear, nonlinear, and with structural break) accept the null hypothesis of the unit roots. This means that the time series of budget balance is not stationary (not mean reverting characteristic), and therefore cannot sustain the budget deficit in Algeria over the long term. This suggests that Algerian government needs to pay more attention to the fiscal policy and efficiently control the budget deficit to avoid the debt crisis.
Keywords: E62; H62; C22; 330; Fiscal policy; Sustainability; Structural breaks; Nonlinear model; Stationarity